Društveni locus utopijskog - Ciglar-Žanić, Janja (Array, 1997)
The paper focuses on the social-cultural and aesthetic elements that made Renaissance philosophers and writers use the utopian genre and motives. The authoress starts from the following basic tenets: First, that - in keeping with the change of the world-view - the Renaissance utopian genre replaced the Medieval apocalyptic vision of the world, becoming the dominant mode of construing the (ideal) social system, an "imaginative vision of the telos of social life" (N. Frye) and thus a particularly appropriate form of critical commentary to the contemporary society, politics and culture. Second, that the motivation behind the frequent uses and adaptations of the utopian genre during the Renaissance are common to Renaissance philosophers, social thinkers and writers alike, in view of the potential qualities of the genre and of the focal points of the novel world-view. In this context, the authoress pays special attention to Petrić's "La citta felice", More's "Utopia", Držić's comedy "Dundo Maroje" and Shakespeare's dramatic 'romance' "The Tempest".